2018
DOI: 10.1002/adfm.201706567
|View full text |Cite
|
Sign up to set email alerts
|

Centimeter‐Sized Cs4PbBr6 Crystals with Embedded CsPbBr3 Nanocrystals Showing Superior Photoluminescence: Nonstoichiometry Induced Transformation and Light‐Emitting Applications

Abstract: An HBr‐assisted slow cooling method is developed for the growth of centimeter‐sized Cs4PbBr6 crystals. The obtained crystals show strong green photoluminescence with absolute photoluminescence quantum yields up to 97%. More importantly, the evolution process and structural characterizations support that the nonstoichiometry of initial Cs4PbBr6 crystals induce the formation of nanosized CsPbBr3 nanocrystals in crystalline Cs4PbBr6 matrices. Furthermore, high efficiency and wide color gamut prototype white light… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

22
339
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 271 publications
(364 citation statements)
references
References 47 publications
22
339
3
Order By: Relevance
“…102 Blue-emitting Cs 4 PbBr 6 composites were only very recently reported by Chen et al, who were able to synthesize both blue- and green-emerging Cs 4 PbBr 6 cm-sized single crystals embedded with CsPbBr 3 NCs. 34 Here, it was observed that during the crystallization first small blue-emitting NCs were formed. Interestingly, it was reported the blue PL slowly shifted toward the green, even if the single crystals were isolated from their growth media, thus indicating that small blue-emitting CsPbBr 3 NCs are thermodynamically less stable than the larger green-emitting CsPbBr 3 NCs.…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…102 Blue-emitting Cs 4 PbBr 6 composites were only very recently reported by Chen et al, who were able to synthesize both blue- and green-emerging Cs 4 PbBr 6 cm-sized single crystals embedded with CsPbBr 3 NCs. 34 Here, it was observed that during the crystallization first small blue-emitting NCs were formed. Interestingly, it was reported the blue PL slowly shifted toward the green, even if the single crystals were isolated from their growth media, thus indicating that small blue-emitting CsPbBr 3 NCs are thermodynamically less stable than the larger green-emitting CsPbBr 3 NCs.…”
mentioning
confidence: 95%
“…38 Moreover, several groups have used transmission electron microscopy (TEM) to identify the presence of green luminescent CsPbBr 3 NCs in Cs 4 PbBr 6 microcrystals, as well as in Cs 4 PbBr 6 NC solutions (Figure 2e). 30,31,34,62 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[120] Very recently, we developed a HBr-assisted slow cooling method to fabricate Cs 4 PbBr 6 single crystallites with embedded CsPbBr 3 NCs. [121] as depicted in Figure 8a,b. PbBr 2 and CsBr with molar ratio of 1:4 was dissolved in a fixed mixture of DMF and HBr (Volume ratio 5:4).…”
Section: In Situ Fabricated Pncs Embedded In Crystalline Matrixmentioning
confidence: 99%
“…Reproduced with permission. [17,51,53,59,67,78,88] Copyright 2014-2017, American Chemical Society; [57] Copyright 2015, American Association for the Advancement of Science; [58] Copyright 2012, The Chemical Society of Japan; [63,65] Copyright 2016, Springer Nature; [62,[70][71][72]117,121] Copyright 2015-2018, Wiley-VCH. mesostructured films through sol-gel treatment of TiO 2 and SiO 2 precursors within organic templating agents.…”
Section: Hard Template Assisted In Situ Fabricationmentioning
confidence: 99%